Social media apps on the Camino de Santiago - Sixto-García, José (Frontiers in Communication, 2025)
IntroductionThe Camino de Santiago continues to beat records in terms of number of pilgrims and increases their popularity internationally, since there are already more foreign than Spanish pilgrims. On the other hand, the use of social media (instant messaging apps and social networks) also continues to grow worldwide. It is assumed that pilgrims take a mobile phone with them on the Camino, but what apps do they use? Do these apps make them feel safer during the pilgrimage?MethodsThrough surveys of pilgrims and in-depth interviews, this research provides answers to these questions.Results and discussionThe results show that pilgrims use more messaging apps than social networks and the use of both as protection mechanisms during the Camino de Santiago. It also warns of the possibility that pilgrims, especially foreigners, may be transmitting perceptions of insecurity while on the pilgrimage, which would damage the public image of the Camino.